Pencatatan Pernikahan dan Batas Usia Pernikahan di Negara Muslim - Pratiwi Uly Romadhoni; Dina Sakinah Wijaya (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
Talking about Islamic Family law in the Muslim World as we know it, the provisions of all countries ar not the same. There are similarities but only a few. The similarity of these provisions starts from the pillars and terms, and also the existence of the same marriageable age. However, there are also some differences. Some countries also do not provide specific provisions. These provisions are only a formal requirement to legalize marriage. Therefore, marriage can be legalized in the eyes of law and religion. The implementation of Islamic family law in Muslim countries varies in terms of legal rules, legal practices, and legislation adopted by each country that identifies itself as an Islamic state or has a majority Muslim population. This diversity is caused by differences in the situations, conditions, and cultural backgrounds of the societies in these countries. Keywords: marrage law, marriage registration, marriage age limit